2019
DOI: 10.1155/2019/2384069
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropins and Their Association with the Risk of Prediabetes and Type 2 Diabetes in Middle-Aged Postmenopausal Women

Abstract: Recent studies have suggested that a low concentration of follicle-stimulating hormone (FSH) is associated with a higher prevalence of metabolic disturbances in postmenopausal women. In this study, we aim to evaluate the association between FSH, luteinizing hormone (LH), and LH/FSH ratio values and the risk of insulin resistance (HOMA-IR >2.0), prediabetes (IFG), and type 2 diabetes in a 5-year prospective study in postmenopausal women. 114 postmenopausal women were divided into 4 groups: group 1 (baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Further analysis showed that FSH was independently associated with the LAR in our postmenopausal women. Taken together, our results support that a higher FSH level was associated with lowering insulin resistance and diabetes in postmenopausal women [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Further analysis showed that FSH was independently associated with the LAR in our postmenopausal women. Taken together, our results support that a higher FSH level was associated with lowering insulin resistance and diabetes in postmenopausal women [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 83%
“…FSH was significantly associated with adiponectin levels in the non-BrCa group ( p < 0.001) after adjusting for age, BMI, and menopause duration. These results indicate that adiponectin might be a link between FSH and metabolic disorders, such as insulin resistance and prediabetes, in postmenopausal women [ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies have demonstrated that prediabetes was an impaired glucose regulation state which mainly caused by the pancreatic β cell dysfunction with insulin secretion and hepatic insulin resistance (IR) cell damage [ 19 , 20 ]. Besides, people with prediabetes have a high risk of developing diabetes mellitus, especially T2DM [ 21 ]. Numerous researches have indicated that PI, TI, 25(OH) D3, and WC were associated with the occurrence of T2DM [ 5 , 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that low levels of FSH are associated with increased risk of metabolic abnormalities in postmenopausal women. [ 42 ] The possible reasons are, the higher estrogen in obese postmenopausal women leading to aromatization of androgens to estrogens in adipose tissue, which suppresses FSH secretion. In addition, other compounds such as follistatin and activin may influence the FSH level and simultaneously regulate insulin sensitivity and chronic inflammatory status.…”
Section: B Ackgroundmentioning
confidence: 99%